ANALISIS KIMIA 75 JENIS KAYU DARI BEBERAPA LOKASI DI INDONESIA - Tjutju Nurhayati Syahri (Jurnal Penelitian Hasil Hutan, 1988)
The result of chemical analyses of 205 wood species has been published in previous reports.  The analyses comprised determination of content of cellulose, lignin, pentosan, ash, solubility in alcohol benzene 1:2, hot and cold water and In 1:2 sodium hydroxide. As a continuation of the above work, the result of chemical analyses of 75 wood species is presented in this report.The analyses reveal that cellulose content ranges from  40.58-62.50  percent, lignin from  21.10-35.03 percent, pentosan from 8.90-19.96 percent and ash from 0.08-3.40 percent. The solubility in alcohol benzena 1  :  2 ranges from  0.54-11.90 percent, hot water 0.39-12.95 percent and 1% natriumhidroxide from 0.50-22.27 percent. There are 43 wood species with cellulose content above 45 percent, 8 species with lignin content above 33 percent, and there are respectively 25 and 39 wood species with solubility in alcohol benzena 1 : 2 and hot water above 4 percent.